Improving Anthropometric and Nutritional Status among School-Aged Children through Animal Source Food-Snack Intervention - Kustiani, Ai; Khalida Dalimunthe, Nathasa; Woro Astuti, Dewi; Syukrina Puteri, Hidayatusy; Nurhartanto, Adhi; Hervidea, Radella (Indonesian Journal of Human Nutrition, 2026)
Approximately 49.2% of children consume animal-source food (ASF) derived from ultra-processed products. Unhealthy eating habits established during childhood may shape unhealthy eating behaviors. This study aimed to analyze the effect of an ASF snack intervention on anthropometric indicators and nutritional status among school-aged children in Central Lampung Regency. This research used a one-group pretest-posttest design conducted in elementary schools in Central Lampung Regency, Lampung, from August to October 2024. A total of 240 subjects participated in the study. Data collected included subject and parental characteristics, body weight, height, and nutritional status indicators based on Height-for-Age Z-score (HAZ) and BMI-for-Age Z-score (BAZ). The intervention consisted of providing 20 ASF snack menus within a 10-day menu cycle, administered three times per week for approximately 6.6 weeks. Data were analyzed using paired t-tests with a significance level of 5%. There was no significant change in body weight (p=0.096), but height increased significantly by approximately 2.82 cm (p<0.001). HAZ also improved significantly by +0.41 SD (p=0.000), indicating a shift from stunted to normal nutritional status. In contrast, BAZ decreased significantly by approximately -0.21 SD (p=0.006), remaining within the normal category. School-based ASF snack interventions implemented for approximately 6.6 weeks may contribute to improvements in height and nutritional status based on HAZ and BAZ indicators among school-aged children.